2006
DOI: 10.1111/j.1420-9101.2005.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Host resistance and parasite virulence in greenfinch coccidiosis

Abstract: The question why different host individuals within a population differ with respect to infection resistance is of fundamental importance for understanding the mechanisms of parasite‐mediated selection. We addressed this question by infecting wild‐caught captive male greenfinches with intestinal coccidian parasites originating either from single or multiple hosts. Birds with naturally low pre‐experimental infection retained their low infection status also after reinfection with multiple strains, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
(101 reference statements)
2
24
3
1
Order By: Relevance
“…This finding implies that steatocrit enables to identify much more subtle effects on digestion than measurement of oocyst shedding or circulating fats. It also confirms the previous finding in the same model system that new, heterologous parasite strains appear more virulent than familiar strains (Hõrak et al., 2006). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding implies that steatocrit enables to identify much more subtle effects on digestion than measurement of oocyst shedding or circulating fats. It also confirms the previous finding in the same model system that new, heterologous parasite strains appear more virulent than familiar strains (Hõrak et al., 2006). …”
Section: Discussionmentioning
confidence: 99%
“…We thus predicted that (i) treatments with toltrazuril and sulfadimethoxine result in decrease in steatocrit values as compared to untreated control birds. We have also shown that infecting greenfinches with novel coccidian strains originating from multiple hosts cause decline in body mass and plasma triglyceride levels (Hõrak, Saks, Karu, & Ots, 2006). Hence, we predicted that (ii) such experimental infection will result in increase in steatocrit as compared to untreated control birds.…”
Section: Introductionmentioning
confidence: 99%
“…The coccidian species present in the feces of migrating greenfinches in Estonia has been previously identified as Isospora lacazei (for details, see Hõrak et al, 2004). Coccidian-infection intensities (number of oocysts per gram of feces) of individual greenfinches were quantified as described previously (Hõrak et al, 2004;Hõrak et al, 2006;Saks et al, 2006). Infection intensities were determined on days 4, 6, 8, 10, 12, 16, 18, 20-22, 24-34, 36, 37, 39, 41, 44, 47 and 48 of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been mostly adopted for hosts with asexual reproduction where clones can be easily infected with different parasite strains [47]. One of the rare studies, dealing with a bird species, addressing the importance of genetic variation among hosts and parasite strains for the outcome of the interaction has been recently published by Hõrak et al [48]. They experimentally infected greenfinches (Carduelis chloris) with single and multiple coccidian strains (Isospora lacazei).…”
Section: Environmental Effects Modulating the Cost Of Infectionmentioning
confidence: 99%